The importance of technology in banking during a crisis - Niccola Pierri; Yannick Timmer (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
We study the implications of information technology (IT) in banking for financial stability, using data on US banks' IT equipment and the tech-background of their executives. We find that one standard deviation higher pre-crisis IT adoption led to 10% fewer non-performing loans during the global financial crisis. We present several pieces of evidence that indicate a direct role of IT adoption in strengthening bank resilience; these include instrumental variable estimates exploiting the historical location of technical schools. Loan-level analysis reveals that high-IT adoption banks originated mortgages with better performance and did not offload low-quality loans.
Keywords: O3; G21; G14; E44; D82; D83; 330; Technology; Financial Stability; IT Adoption; Non-Performing Loans